KAWIN PAKSA DALAM PERSPEKTIF FIQH ISLAM DAN GENDER - Misbakhul Munir; Ahmad Subekti; Dzulfikar Rodafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
AbstractIn married life in the daily life of marriage is a necessity for mankind, that's why if there is a male or female household to use a lot of consideration for the choice of their children in determining the match, the bride and groom who will carry out the marriage and the guardian or parents the act of forcing their children to force marriage means forced marriage. Forced marriages are parents arranged or forced children to marry without the consent and willingness of the child and not his right to choose his partner. In Islamic law there is no compulsion for someone to marry with the choice of their parents. The concept of gender as an act of forced marriage which is considered as a discrimination against women. Keywords: forced marriage, the concept of gender